1970
DOI: 10.1115/1.3425055
|View full text |Cite
|
Sign up to set email alerts
|

Mean Flow Calculations Behind Arbitrarily Spaced Cylinders

Abstract: A finite array of arbitrarily spaced parallel rods is considered. It is assumed that momentum deficit may be superposed locally. The momentum deficit is computed behind each cylinder—considering it as a single cylinder—using one of the accepted theories. Then the momentum deficits at each point due to all the cylinders are superposed. From this an overall velocity distribution is calculated. Experiments with various rod diameters and spacings were conducted. The results were within 3 percent of the theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Associate Professor of Mechanical Engineering, University of Toronto, Toronto, Canada 3. Even at large Reynolds numbers, we can expect identifiable large eddy patterns, i.e., turbulent vortices, to exist for the near wake region of the flow.4 -Cylinder Reynolds number was approximately 10,000, comparable to the present investigation.Journal of Basic Engineering DECEMBER 1971 / 499Copyright © 1971 by ASME Downloaded from http://asmedigitalcollection.asme.org/fluidsengineering/article-pdf/93/4/500/5617613/499_1.pdf by guest on 03 September 2020…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Associate Professor of Mechanical Engineering, University of Toronto, Toronto, Canada 3. Even at large Reynolds numbers, we can expect identifiable large eddy patterns, i.e., turbulent vortices, to exist for the near wake region of the flow.4 -Cylinder Reynolds number was approximately 10,000, comparable to the present investigation.Journal of Basic Engineering DECEMBER 1971 / 499Copyright © 1971 by ASME Downloaded from http://asmedigitalcollection.asme.org/fluidsengineering/article-pdf/93/4/500/5617613/499_1.pdf by guest on 03 September 2020…”
supporting
confidence: 75%
“…These nonlinear mechanisms are not defined but presumably the remarks refer to possible interaction of the turbulent vortex systems from adjacent wakes. 3 Work presently being carried out by M. D. Palmer at Toronto would support this view. It has been found that pairs of cylinders of differing diameter and with spacing of the order of the largest cylinder, shed a, complicated wake pattern with some quite novel features.…”
Section: James F Keffermentioning
confidence: 88%